Contingency Theory and Public Emotions in Crisis Communication –A Conceptual Study - Rose, Rainy; V. Vijay Kumar; Kesari Jena, Lalatendu (Journal of Education Culture and Society, 2023)
Aim. Problems are inevitable in the subtleties of organizational communication, but it does not mean confronting them is uncontrollable. This paper aims to offer a conceptual structure for investigating contingency theory in Public Relations (PR) during an organizational crisis. The research investigates PR practitioners’ use of advocacy and accommodation in contingency theory to intervene in crisis communication. It also offers insights into the public’s emotional response and coping mechanisms during a crisis, as well as how understanding these emotions (such as anger, anxiety, fear, and grief, among others) could aid PR professionals in developing more effective crisis communication methods. Method. Empirical research was conducted on the basis of literature reviews by observing and analyzing the existing literature on contingency theory, crisis communication in organizations, and public emotions. Results. This conceptual paper proposes and empirically tests a few propositions. The implications for future studies are included in the paper. Findings promote the adopting a dual-continuum strategy that might assist public relations professionals in preferring superior crisis management strategies for obtaining desired organizational outcomes. Conclusion. The authors assert that PR professionals must move from embracing Grunig’s four models of excellence to contingency theory for communicating strategically with the public. The authors propose to adopt a dual-continuum approach that varies from advocacy to accommodation and might provide practical guidance to choose a better stance adopted by the organization towards the public during a crisis. The negative emotions of the public influenced by a crisis along with their emotional coping approaches are also discussed.